CLUSTER MODEL MANAGEMENT SYSTEM OF BIOENERGY MARKET DEVELOPMENT - Shelenko, D.I.; Balaniuk, I.F.; Matsola, M.M.; Sas, L.S.; Nemish , D. V. (The actual problems of regional economy development, 2020)
The article is aimed at studying the peculiarities of the formation of a cluster model of bioenergy market development. The expediency of deepening clustering at different levels of government in Ukraine has been proved. It is determined that the most expedient direction of solving the problem of the cluster model of bioenergy market development is the search and use of renewable energy sources. The importance of clustering to support the organizational elements of management of production processes and the use of alternative renewable fuels, which will be a prerequisite for increasing the production of biomass of agricultural origin. The structural construction of the organization of management of cluster model of development of the bioenergy market has been offered. The purpose of the article is to study the organization of cluster model management of the bioenergy market. In the course of research, the methods of scientific abstraction were used - to single out the preconditions for the revival of market activity of clusters in the bioenergy market of Ukraine and the system-synergetic approach - in order to study bioclusters. The expediency of taking into account two groups of factors of endogenous and exogenous genesis to achieve the expected intermediate and final results of the cluster model of bioenergy market development is substantiated. It has been proved that the creation of specialized clusters should be based on awareness and formation of not only individual but also general responsibility for the effectiveness of the relevant area of work. It is extremely important that a deep awareness of the need for clustering is gradually manifested in the formation of a favorable environment for its formation and development. Has been established that the defining stage of development of the cluster model of the bioenergy market is the study of the real state of the cell in which the system operates.